Teaching Vocabulary Using Word Wall Media - Sri Utari; Dewi Syafitri; Sastika Seli (EDULIA: English Education, Linguistic and Art Journal, 2020)
The purpose of this study was to determine the effectiveness of learning vocabulary using word wall media for seventh grade students of SMP Negeri Selangit in the 2018/2019 Academic Year. This research method is pre-experimental with one group pre-test and post-test design. The results showed that there were four main findings, namely the student’s scores on the pre-test 51.25, the student's scores on the post-test 70.53. The normality in the pre-test was 3,200 and 11,070, while the post-test results showed 5,427 and 11,070 and the result of the paired t-test calculation was 11.14. In conclusion, learning vocabulary using word wall media is significantly effective in class VII students of SMP Negeri Selangit in the 2018/2019 Academic Year. Keywords: Teaching, Vocabulary, Word Wall Media